CFD-DEM simulation of heat transfer in fluidized beds: Model verification, validation, and application - Wang, Shuai; Luo, Kun; Hu, Chenshu; Lin, Junjie; Fan, Jianren (Chemical engineering science, 2019)
•Verification, validation, and application for the CFD-DEM method coupled with heat exchange are conducted.•Fluid velocity and particle diameter have a more remarkable influence on convection than conduction.•Particle temperature in the riser and the system presents a two-peak histogram distribution. For a single isolated particle, the effect of overlap displacement on conduction and the effect of particle diameter/fluid velocity on convection are comprehensively studied using a CFD-DEM method coupled with heat exchange. Moreover, the model is further validated in a pseudo-2D bubbling fluidized bed and the influence of operating parameters (i.e., fluid velocity, particle diameter, and mass loading) on heat transfer contribution is deeply revealed. The results show that the fluid velocity and particle diameter have a more remarkable influence on convective heat transfer than conductive heat transfer. Besides, the particle-fluid convection dominates the heat transfer while the particle-particle conduction is almost negligible. The particle-fluid-particle conduction occupies about 10% of the total heat transfer. Finally, the model is successfully applied in a circulating fluidized bed. The average mass fractions of solid materials in the riser, cyclone, and dipleg are 0.737, 0.023, and 0.240, respectively. Solid internal circulations and lower solid velocities in the horizontal part of dipleg lead to a two-peak histogram distribution of particles temperature in the riser and the system.